2022
DOI: 10.1007/s11629-022-7329-2
|View full text |Cite
|
Sign up to set email alerts
|

Mapping the spatial distribution of fossil geothermal manifestations and assessment of geothermal potential of the Tangyin rift, Southeast of Taihang Mountain in China

Abstract: The spatial prediction of geothermal sites along the southeast side of Taihang Mountain in the Tangyin rift is a critical goal in the development of renewable energy resources in cities such as Hebi in Henan province, which has significant potential for geothermal energy production due to the existence of deep faults and Cenozoic volcano. The study aimed to delineate areas with high geothermal manifestations for detailed geothermal exploration and well-test drilling. To define favorable zones for geothermal po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…The study of paleovolcanic terrains in terms of modern volcanology may also provide results that are quite helpful in the study of recent terrains with similar characteristics, where such processes may be inferred, yet not observed directly due to the lack of deep erosion and tectonics. Similarly, the exploration of high-enthalpy geothermal reservoirs in active volcanic areas can greatly benefit from the study of ancient analogs coming from deeply eroded volcanic terrains where the roots of the volcanic edifices are well exposed and the geometry and distribution of fossil geothermal reservoirs can be observed (e.g., [102][103][104]).…”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 99%
“…The study of paleovolcanic terrains in terms of modern volcanology may also provide results that are quite helpful in the study of recent terrains with similar characteristics, where such processes may be inferred, yet not observed directly due to the lack of deep erosion and tectonics. Similarly, the exploration of high-enthalpy geothermal reservoirs in active volcanic areas can greatly benefit from the study of ancient analogs coming from deeply eroded volcanic terrains where the roots of the volcanic edifices are well exposed and the geometry and distribution of fossil geothermal reservoirs can be observed (e.g., [102][103][104]).…”
Section: Final Remarks and Future Perspectivesmentioning
confidence: 99%
“…Subsurface exploration techniques must adapt to rely less on surface geothermal features. It is crucial to incorporate accurate geological and geophysical data to delineate subsurface structural features when analyzing geothermal processes [14,32].…”
Section: Geological Setting and Study Area Descriptionmentioning
confidence: 99%
“…Therefore, worldwide researchers have suggested that Remote Sensing (RS) and Geographic Information System (GIS) techniques, including thermal bands on satellite images like Landsat−8 OLI/TIRS, be considered as valuable and cost-effective tools for evaluating geothermal resources. These methods estimate the land surface temperature (LST) and have been employed by researchers to delineate areas with geothermal potential in different geological settings [11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The existence of geothermal energy is generally found in the volcanic zone, which is a weak zone in geology (Cheng, 2022;Farhan et al, 2019;Geoffroy et al, 2022;Mahwa et al, 2022). In this zone, there are many faults formed due to geological activity (Geoffroy et al, 2022;Riziq Maulana et al, 2019;Zaini et al, 2022).…”
Section: Introductionmentioning
confidence: 99%